Zingiberaceae from Plantation Forests as Food and Beverage Additives: A Review - Saefudin; Efrida Basri; Niniek Setyowati (Current Perspectives in Agriculture and Food Science Vol. 6, 2023)
Benefits of Zingiberaceae’s plants for the community residing in rural areas are as food/beverage additives and for human health. The superiority of the plants that belong to the Zingiberaceae is able to grow well under the forest stands at open sites. Relevantly, field observation that involved 30 respondents in the forest villages administratively under the regions of Perum Perhutani (the State-Owned Forest Enterprises) Units I, II, and III (East Java, Central Java, and West Java, respectively) revealed that as many as 10 Zingiberaceae species, i.e. Alpinia galanga L. Willd, Amomum cardomomum Willd, Boesenbergia rotund L. Manst., Curcumma domestica L (kunyit), C. xanthorrhiza Robx, C. heyneana Val. & van Zijp, Etlingera elatior (Jack.) R. M. Sm., Kaemferia galanga L, Zingiber oficinale Rosc, and Z. zerumbet (L) Rosc were already used as food/beverage additves consumed by the comminity in the vicinity of production forests. The additives from Zingiberaceae were categoryzed safe to be consumed as ingedients/dressings, coloring agents, and healthy aroma for food/beverages. The cultivation of Zingiberaceae to grow in production forests could bring economy values and positive impacts on the community and environments of production forests. Several ingedients of food/beverages from Zingiberaceae have been modified into the contemporary recipes favored as special menu at the Perhutani’s culinary tourism sites and modern restaurants. The prospects of Zingiberaceae were able to develop productive business and economy at forest villages as well as to maintain the sustainability/continuity of production forests.